SIFAT PEMESINAN 36 JENIS KAYU DARI DAERAH IRIAN JAYA - Osly Rachman; Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
This article presents test results of the machining properties of 36 wood species from Manokwari, lrian Jaya. The test method used was the modified ASTM D-1666 described in Forest Products Research Institute Report No.160 (1982). In most of the species 25 or more samples were available for test. All test material was dried to equilibrium Moisture content condition (15 to 18% moisture content). The machining properties that were investigated were planing, shaping, boring, mortising, turning and sanding.Some of the species tested are consistenly better than average in most respects. The species have good machining properties are sehiega.koesigoro, seyam, matoa, kerbai and petian. Whereas some species, such as fofo, sehiye, wafut, basuoh, serakka and bimiek are consistently poorer. The others species are good in some properties and fair or poor in others.